THE GENRE FOLDER IN THE SERVICE OF ENVIRONMENTAL EDUCATION - Rodrigues, Maria Anunciada Nery; Carvalho, Aurean de Paula (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Based on the integration of knowledge about environmental education and language while interaction and social practice, in an interdisciplinary perspective, this study is derived from an extension project developed by teachers and students of IFTO - Campus Porto National, in the year 2012. This article will be described the second stage of the project that aimed to develop a folder with information and guidance on the sustainable use of the water consumed by quilombola community Malhadinha in Brejinho de Nazaré, in the state of Tocantins. To elaborate the folder we rely on the methodology of BACELAR et. al (2009), with some adaptations, following the steps: planning, surveying ideas on the subject in question; selection of non-textual elements, distribution and dissemination. The results demonstrate that it is possible to combine the teaching of Portuguese to Environmental Education, enabling addressing the cross-cutting themes through working with the textual genres.